Preclinical and experimental evidence of salvianolic acid B in the treatment of neurological diseases - Bi, Shijun; Liu, Shibing; Zhu, Kunyuan; Gao, Dandan; Chen, Ligang; Yu, Chunyong; Liang, Guobiao (Frontiers in Pharmacology, 2025)
BackgroundNeurological diseases such as stroke and Alzheimer’s disease pose increasing challenges to global public health. Salvianolic Acid B (SalB), a major active component of Salvia miltiorrhiza, has garnered attention due to its anti-inflammatory, antioxidant, neuroprotective, and pro-angiogenic properties in neurological disease treatment.PurposeThis paper aims to review the mechanisms and effects of SalB in the treatment of neurological diseases, exploring its role in improving neurological function, mitigating neuroinflammation, and reducing oxidative stress.ResultsSalB demonstrates multifaceted mechanisms in neurological disease management. In animal models of cerebral ischemia/reperfusion injury, SalB reduces infarct size and enhances neurological recovery via anti-inflammatory, anti-oxidative stress, and angiogenic pathways. It protects the blood-brain barrier and inhibits neuronal apoptosis in stroke models. In spinal cord injury models, SalB alleviates edema and promotes motor function recovery. In Alzheimer’s disease models, SalB suppresses amyloid-beta formation and neuroinflammation. Additionally, SalB exhibits antidepressant and analgesic effects in pain-depression comorbidity models. These effects are mediated through the regulation of signaling pathways, including NF-κB, AMPK, PI3K/Akt, and Nrf2, highlighting SalB’s broad therapeutic potential in neurological diseases.ConclusionSalB exhibits promising prospects in the treatment of neurological diseases. However, its clinical application faces challenges such as chemical stability and bioavailability. Further research on the mechanisms of SalB and innovative drug delivery strategies is needed to advance its application in neurological disease therapy.